Lack of consensus on tests and criteria for generalized joint hypermobility, Ehlers–Danlos syndrome: Hypermobile type and joint hypermobility syndrome. Issue 3 (24th January 2014) - Remvig, Lars; Flycht, Lise; Christensen, Karl B.; Juul‐Kristensen, Birgit
<x xml:space="preserve">Abstract</x> The objectives of this study were to register clinicians performance and opinion of importance of clinical tests for generalized joint hypermobility (GJH), Ehlers–Danlos syndrome, hypermobility type (EDS‐HT) and joint hypermobility syndrome (JHS), and to reach a consensus among clinicians on criteria for diagnosing GJH, EDS‐HT and JHS. A panel of clinicians answered questions about how to perform and interpret clinical tests and rated test importance on an 11‐box scale. The questionnaire was developed on the basis of information from focus groups and the literature. Cronbach's α was used as a measure of internal consistency/consensus among the panelists. The results showed Cronbach's α on importance score of items for diagnosing GJH, EDS‐HT and JHS was 0.61, 0.79, and 0.44, respectively. Panelist‐group correlation for the three conditions varied substantially (−0.46 to 0.89, 0.03 to 0.68, and −0.07 to 0.68) indicating heterogeneity among the panelists. There was agreement on which tests to use, but performance of the tests (i.e., the specific maneuvers) varied considerably inclusive use of tests with unknown reliability. Furthermore, agreement on the diagnostic criteria varied. We conclude that the level of consensus for the importance of various items for diagnosing GJH, EDS‐HT and JHS, was below the required limit (Cronbach's α >0.90) for clinical decision‐making and diagnosing. Consensus on tests and criteria through a Delphi process could not be reached. Better descriptions of, and reliability studies on, test maneuvers and criteria sets for these conditions are needed. Subsequent intensive training and implementation of these tests and criteria, nationally as well as internationally should be established. © 2014 Wiley Periodicals, Inc.